Exploring the postpartum return to sport and performance in Canadian elite athletes - Hewitt, Chloe M.; Campbell, M. Karen; Choi, Yun-Hee; Thornton, Jane S. (Frontiers in Sports and Active Living, 2025)
BackgroundAthlete-mothers in elite sport were viewed as anomalies until very recently. Perhaps as a consequence of limited research, support and resources available for pregnant and postpartum athletes may be inadequate.ObjectiveTo explore the experiences of athletes returning to sport and performance postpartum.MethodsTen elite Canadian athletes who became pregnant during their sporting career and attempted to return to competitive sport after childbirth completed an online questionnaire.ResultsMost participants reported that timing of conception was planned around competition schedule. During pregnancy, most athletes trained through pregnancy, but found the advice they received unsatisfactory. Lack of support for childcare within sport and balancing breastfeeding with training were commonly identified challenges. Nine of the 10 athletes reported resuming training after childbirth and five returned to competitive sport, of which four reported improved performance.ConclusionElite athletes in our sample were able to return to a high level of sport after childbirth, however many expressed the need for improved support through pregnancy and the postpartum period. This exploratory study reveals promising findings of how experiences are improving for pregnant and postpartum elite athletes. This sets the stage for more research to promote sport participation by athlete mothers.